Validitas Pengembangan Media Pembelajaran Interaktif “Sikarji” pada Materi Kebudayaan Daerah Jawa Timur Siswa Kelas V - Khoirun Nisa’; Frans Aditia Wiguna; Karimatus Saidah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study was motivated by the low level of engagement and understanding among fifth-grade students at SDN Mrican 1 regarding the Pancasila Education subject, specifically the topic of East Java regional culture. Instruction dominated by lecture methods and limited media led to student boredom, a lack of focus, and difficulty retaining information, despite the school possessing technology-based learning facilities that had not been optimally utilized. This study aimed to determine the validity of the